DETERMINATION OF ECONOMIC AND STRUCTURAL FACTORS AFFECTING ANGORA GOAT BREEDING: THE CASE OF ANKARA - Mehmet Arif ŞAHİNLİ; Ahmet ÖZÇELİK; Hüseyin T. GÜLDAL (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The objective of this paper is to determine the changes on some performance of the Mohair (Ankara) goats farming system during 2017-2018. In this study, we examine production of the goats farms of Ankara province. Economic analysis is implemented by using data from 45 Turkish mohair goat farmers. The gross production value of the establishments is increased for the business groups according to the business groups, ranging from 495,148.74 Turkish Liras (TL) to 731,154.09 TL. According to the average of the establishments, the goat breeding activity is 58.28%, the vegetable production is 40.64% and the sheep breeding activity is 1.08%. In Group 1, the share of the mohair in the value of animal production was 13.03%, while it was 14.37% in group 2. According to the establishment groups, the variable costs for vegetable production varying between 15,346.91 TL and 46,411.88 TL, while this value is 38,818.22 TL for the average of the establishments. According to the establishment groups, the variable costs in animal production vary between 91,127.86 TL and 263,160.36 TL. While the total gross profit per establishment in the examined establishments is between 398,915.15 TL and 560,170.95 TL. There was an employee problem with 30.00%, with feed prices with 26.67% and mohair prices with 25.00%, respectively, in the first group. 18.18% of the establishments in the first group and 12.50% of the establishments in the second group have been educated on herd management. Within the scope of the research, it was determined which supports were used by the establishments and it was determined that earrings and mohair support were used the most according to the results of the research. Within the scope of the research, 61.76% of the establishments in the 1st groups use agricultural loans and this rate is 81.82% in the 2nd group establishments.